(18)F FDG PET/CT Evaluation of Patients with Ovarian Carcinoma - Iagaru, Andrei (2008)
PURPOSE: The role of (18)F FDG PET has been studied in ovarian carcinoma, but its sensitivity and specificity calculations are based on dedicated PET acquisition, not PET/CT in the majority of the published studies. Therefore, we were prompted to review our experience with PET/CT in the management of patients with ovarian carcinoma. MATERIALS AND METHODS: This is a retrospective study of 43 women with ovarian carcinoma, 27–80 years old (average: 53.9 ± 7.8), who had whole-body PET/CT at our institution from Jan 1(st), 2003 to Aug 31(st), 2006. We reviewed the patients’ outcomes from medical records and compared them to the interpretation of the PET/CT scans. Sensitivity and specificity were calculated using a 2 × 2 table with pathology results (79.1% of the patients) or clinical follow-up (20.9% of the cases) as the gold standard. Confidence interval (CI) estimations were performed using the Wilson score method. RESULTS: All patients had advanced stage ovarian cancer and the study was requested for re-staging. A total of 60 scans were performed: 30 pts had 1 scan, 9 pts had 2 scans and 4 pts had 3 scans. The administered doses of (18)F FDG ranged 381.1 – 769.6 MBq (average: 569.8 ± 73.3). PET/CT had a sensitivity of 88.4% (95% CI: 75.1–95.4) and a specificity of 88.2% (95% CI: 64.4–97.9) for detection of ovarian cancer. The SUV max of the detected lesions ranged 3–27 (average: 9.4±5.9). The CA-125 tumor marker ranged 3–935 kU/ml (average: 265.2) in patients with positive scans and 4–139 kU/ml (average: 17.1) in patients with negative scans. This difference was statistically significant (P value: 0.0242). CONCLUSION: This study confirms the good results of (18)F FDG PET/CT for identification of residual/recurrent ovarian cancer, as well as for distant metastases localization. PET/CT should be an integral part in evaluation of patients with high risk ovarian cancer or rising values of tumor markers (CA-125), prior to selection of the most appropriate therapy.